Surfacing the social factors early: A sociotechnical approach to the design of a future submarine - Boeing, Alexandra; Jorristma, Karina; Griffin, Mark; Parker, Sharon (2020)
Socially oriented approaches to work systems design are increasingly important as new and disruptive technologies become more prevalent. Existing approaches used by organisations to integrate such technologies are often techno-centric and do not adequately consider human issues. Sociotechnical systems (STS) tools are intended to ensure that the technical and organisational aspects of a system are considered together, and given equal attention. However, they are predominately applied late in the design process, limiting their impact. In this article, we outline an STS approach to the early-phase development of a complex work system. The case study illuminates how an STS approach can facilitate the inclusion of socially oriented factors into the design process. We close with recommendations to guide the early-phase application of STS principles in other industries and contexts.